GPS & Galileo :dual RF front-end receiver and design, fabrication, and test /Jaizki Mendizabal Samper, Roc Berenguer Pérez, Juan Meléndez Lagunilla. - Mendizábal Samper, Jaizki.
Includes bibliographical references (p. 179-182) and index.